Tyr1 and Ile7 of glucose-dependent insulinotropic polypeptide (GIP) confer differential ligand selectivity toward GIP and glucagon-like peptide-1 receptors - Moon, Mi Jin; Kim, Hee Young; Kim, Sin Gon; Park, Juri; Choi, Dong Seop; Hwang, Jong-Ik; Seong, Jae Young (Molecules and cells, 2010)
Glucagon like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) are incretin hormones released in response to food intake and potentiate insulin secretion from pancreatic β cells through their distinct yet related G protein-coupled receptors, GLP1R and GIPR. While GLP-1 and GIP exhibit similarity in their N-terminal sequence and overall α-helical structure, GLP-1 does not bind to GIPR and vice versa. To determine which amino acid residues of these peptide ligands are responsible for specific interaction with their respective receptors, we generated mutant GIP in which several GLP-1-specific amino acid residues were substituted for the original amino acids. The potency of the mutant ligands was examined using HEK293 cells transfected with GLP1R or GIPR expression plasmids together with a cAMP-responsive element-driven luciferase (CRE-luc) reporter plasmid. A mutated GIP peptide in which Tyr 1 , Ile 7 , Asp 15 , and His 18 were replaced by His, Thr, Glu, and Ala, respectively, was able to activate both GLP1R and GIPR with moderate potency. Replacing the original Tyr 1 and/or Ile 7 in the N-terminal moiety of this mutant peptide allowed full activation of GIPR but not of GLP1R. However, reintroducing Asp 15 and/or His 18 in the central α-helical region did not significantly alter the ligand potency. These results suggest that Tyr/His 1 and Ile/Thr 7 of GIP/GLP-1 peptides confer differential ligand selectivity toward GIPR and GLP1R.